How do irrigation district managers deal with climate change risks? Considering experiences, tipping points, and risk normalization in northern Italy - Ricart, Sandra; Gandolfi, Claudio; Castelletti, Andrea (Climate risk management, 2024)
Agriculture is one of the most sensitive and vulnerable activities to climate variations; climate change impacts crop yield, soil processes, water availability, and pest dynamic. Farmers are on the front lines of climate change-induced stressors, shifts, and shocks, having to provide solutions as planners, performers, and innovators working under challenging and uncertain risk conditions. Extensive research has been carried out to deepen farmers’ behavior on risks posed by climate change. However, less attention was paid to irrigation district managers, even though their essential role in guaranteeing hydraulic safety, ensuring water supply, even as on-site observers of farmers’ behavior. This paper seeks to uncover the attitudes and actions of irrigation districts managers towards climate change, and their ability to gather significant information on the climate experiences of farmers in the Lombardy region, Italy. Employing a mix of semi-structured interviews and questionnaires, the exploratory approach gathered insights from the managers of the 12 public irrigation districts tasked with governing irrigation development and water management in the region. The study reveals that managers are cognizant of the shifting climate caused by warmer temperatures and extreme weather events, implementing both hard (e.g. water infrastructure maintenance, water storage) and soft (climate and weather services) adaptation countermeasures. Through their own experiences, managers brought to light the driving factors behind farmers’ willingness to adopt water-saving techniques or adapt their crops, despite facing obstacles (e.g. financial investment, institutional support). In addition, the identification of tipping points related to water scarcity and security is coupled with managers and farmers’ trust in technological solutions to partially counteract risk normalization. In line with the findings, suggestions were put forth to enhance managers’ adaptive capacity.